Analisis Faktor-Faktor yang Mempengaruhi Sektor Moneter Berdasarkan Jumlah Uang yang Beredar Pada Statistik Ekonomi dan Keuangan Indonesia (SEKI) - Dian C. Rini Novitasari (Jurnal Matematika MANTIK, 2017)
One of the impacts of the economic crisis that occurred in Indonesia was influenced by the monetary sector that moved the macroeconomy into the economy of the society such as currency rate of exchange and rate of interest policies applied in all banks in Indonesia. Analysis of the factors that influence the money supply is one step that can be used to analyze economic statistics and the financial condition of Indonesia. The analysis begins with finding the regression equation using a nonlinear regression model of several factors used such as foreign activities, bills to the central government, bills to the private sector, and the value of Gross Domestic Product (GDP). Other tests were also carried out such as the data normality test, heteroscedasticity test, and autocorrelation test to read data characteristics used in the 1999-2016 period using SPSS and then analyzed. Where the results obtained in the regression of the central government independent variables do not have a significant effect, the data normality test shows that the data is normally distributed, heteroscedasticity does not occur, and the data does not contain autocorrelation.